Palliative care for case managers: Building capacity to extend community-based palliative care to underserved older adults. Issue 2 (3rd April 2022) - Gardner, Daniel S.; Doherty, Meredith; Ghesquiere, Angela; Villanueva, Carolina; Kenien, Cara; Callahan, Jean; Reid, M. Cary
ABSTRACT: Palliative care has demonstrated effectiveness in alleviating the biological, emotional, social, and spiritual symptoms that accompany serious illness, and improving quality of life for seriously ill individuals and their family members. Despite increasing availability, there are significant disparities in access to and utilization of palliative care, particularly among diverse, low-income, and community-dwelling older adults with chronic illness. Training frontline service providers is a novel approach to expanding access to palliative care among underserved elders. This article presents a process and outcome evaluation of a palliative care curriculum that was developed and piloted for geriatric case managers in a large urban area. We describe the background, planning, design, implementation, and preliminary outcomes associated with a pilot implementation of the curriculum. We conclude with implications for replicating efforts to enhance frontline providers' knowledge, skills, and self-efficacy in extending palliative care to communities that lack access to critical supports for their burdensome symptoms.